Measuring the average velocity and acceleration of a moving object on an inclined plane using a magnetic sensor on a smartphone. (1st January 2023) - Dumrongkitpakorn, Pollawat; Khemmani, Supitch; Plaipichit, Suwan; Wicharn, Surawut; Puttharugsa, Chokchai
Abstract: This paper demonstrates an alternative method to measure the time interval of a moving object in linear motion using the magnetic sensor of a smartphone. The smartphone is stationary and records the magnetic field as a function of time from a moving object with attached magnetic buttons. The value of time interval is then measured and both velocity and acceleration are calculated for the moving object. This method prevents the smartphone from being damaged. The proposed experiment is easy to set up with available objects, and students can conduct this experiment at home.